Влияние климатических факторов на эффективность утилизационной металлогидридной установки двухтопливного малооборотного ДВС газовоза - Чередниченко, Александр Константинович; Ткач, Михаил Романович (НТУ "ХПИ", 2017)
Проанализирована возможность применения сжиженного природного газа в судовой энергетике. Выявлена перспективность утилизации сбросного тепла малооборотных дизельных двигателей применением металлогидридных установок непрерывного действия. Представлена расчетная схема установки и параметры рабочих сред. Приведены результаты математического моделирования процессов в утилизационной металлогидридной установке. Выявлена устойчивость работы утилизационной металлогидридной установки в различных климатических условиях эксплуатации.

Contemporary tendencies in the development of ship power engineering have been analyzed. Consideration was given to the specific features of the transportation of liquefied natural gas by gas tankers. The prospects of utilization of the secondary energy resources of marine double-fuel low-speed diesel engines were defined. The metal hydride units of a continuous action were offered for this purpose. The need for the estimation of the influence of climatic factors on the efficiency of disposal metal-hydride unit has been defined. We proposed to carry out the investigation using the methods of mathematical simulation. The model takes into consideration the main physical relations, in particular material and thermal balances, the phase equilibrium, and heat-mass transfer processes. A relative power of disposal metal-hydride unit was taken as the efficiency criterion. The investigation was carried out with the regard to the propulsive unit of gas tanker of a Q-max type with the propulsion engine 9G80ME. The design diagram of the unit and the parameters of working media have been presented. The data of mathematical simulation of processes have been given. The disposal metal- hydride unit showed a reliable operation in different climatic operation conditions. A specific power of the disposal unit ranged from 5.7 to 6.2 %. The mechanical power of disposal unit was equal to 2.5 MW that enables the drive of the fuel gas compressor of propulsion engine and attached electric generator.
Influence of climatic factors on the efficiency of disposal metal-hydride unit for the double-fuel low-speed internal combustion engine of gas tankers
Keywords: LNG-газовоз; утилизационная установка; малооборотный двигатель; металлогидридная суспензия; водород; LNG-gas tanker; disposal unit; low-speed engine